PUTUSAN PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA KECELAKAAN LALU LINTAS DITINJAU DARI ASPEK KEADILAN HUKUM - Amos Nofanolo Buulolo (LPPM Universitas Nias Raya, 2026)
A decision made during a court trial based on evidence is known as a criminal decision. A breach of the traffic regulations is considered a criminal in the context of traffic accidents. Traffic accidents may occur as a result of violations. Violation-based actions have the potential to hurt you or other individuals. Justice is a notion or philosophy that alludes to equity, equality, and impartial treatment of every person within the legal system. Decision 29/Pid.Sus/2021/PN. Tire is one of the illegal acts in a traffic collision that leads in death. Normative legal research employing the statutory approach, case approach, and analytical method is the sort of study that is done. Primary, secondary, and tertiary data were used in the data gathering process. Deductive reasoning is employed to arrive at conclusions from the descriptive qualitative data analysis. The choice to penalize the offender of a traffic accident crime is assessed from the perspective of legal justice (Decision Study Number 29/Pid.Sus/2021/PN. Ban), which holds that the decision has damaged someone and does not offer justice for the victim. This opinion is based on study findings and debate. which is the law's intended outcome. The culprit should get a lengthy jail term from the judge in order to bring the victim's suffering to a close, discourage future crimes, and educate the public about the need of exercising caution when operating a vehicle.